Problematika Guru dalam Pembelajaran Bahasa Indonesia pada Kurikulum Merdeka di SMPN 13 Makassar - Prasetiyo, Wisnu Aji; Anshari, Anshari; Usman, Usman (Nuances of Indonesian Language, 2025)
This research aims to examine the internal and external problems faced by teachers at SMPN 13 Makassar. Internal problems include challenges or obstacles that arise within teachers in carrying out their professional duties. Meanwhile, external problems include factors outside the teacher's control that influence performance, such as frequently changing educational policy interventions, and a lack of educational facilities and resources. The research method used is qualitative, involving in-depth interviews and participatory questionnaire. he research results show that internal problems often originate from within teachers who do not fully understand the implementation of the Independent Curriculum, have difficulty compiling teaching modules, are confused about choosing learning media for students, and have difficulty determining formative assessments. Meanwhile, external problems stem from a lack of ongoing training from institutions. Recommendations from this research include increasing training and professional development for teachers, improving educational facilities, and strengthening communication and collaboration between all stakeholders in education. It is hoped that this research can provide insight for policy makers in improving the quality of education at SMPN 13 Makassar.